A eutanásia enquanto problema ético e a questão filosófica da morte - Pacheco, Ângela Elisa Cabral (2022)
Euthanasia is a term originating from Greek (ευθανασία) that could be translated as "good death" or "appropriate death" (etymologically, the "eu" means good, worthy, without suffering, and "thanathos" means death). Since its emergence, euthanasia has been the subject of multiple approaches. It is a complex problem, controversial and full of moral dilemmas. Euthanasia is, par excellence, a bioethical issue, since it involves questions related to the freedom to choose one's own death, the responsibility of agents, the effects of a decision, and the values, judgments and moral convictions of the subject. Moreover, it is an issue that touches on the ontology of the living being and the dignity of living. Moreover, it puts us face to face with the problem of finitude, that is, our condition of being-for-death. This is why euthanasia, before being a medical problem, is, first of all, a philosophical issue. The philosophical reflection on euthanasia and the philosophical problem of death also focuses on the (lack of) quality of life and, even more, on the duty of humanity towards patients in situations of extreme suffering and lacking dignity due to the suffering caused by their morbidity. Dignity also implies ensuring the condition of 'unity' of the subject itself, through an ethical decision that commits, in a responsible way, the other.